Small B-cell lymphoma highly suspicious for splenic marginal zone lymphoma with MYD88 L265P mutation and MYC copy-number gain presenting as severe autoimmune hemolytic anemia: a case report with literature review - Liu, Xiaoyan; Zhang, Guoyang; Ma, Liping (Frontiers in Immunology, 2026)
In indolent small B-cell lymphomas, autoimmune cytopenia and histologic transformation pose important diagnostic and management challenges. MYD88 and MYC abnormalities are rarely reported in splenic marginal zone lymphoma (SMZL), and their role in immune dysregulation and transformation remains unclear. We describe a 44-year-old man with a small B-cell lymphoma highly suspicious for SMZL, who presented with severe warm autoimmune hemolytic anemia, massive splenomegaly, and lymphocytosis. He harbored both MYD88 L265P mutation and MYC copy-number gain within a complex karyotype, in the absence of splenic histology. This case, together with a review of the literature, suggests that such “clinically indolent but genetically high-risk” SMZL-like lymphomas may carry a non-negligible risk of progression and transformation and therefore require close longitudinal monitoring. Further accumulation of similar cases and molecular data is needed to clarify the prognostic and biological impact of MYD88 and MYC alterations in this setting.